2009
DOI: 10.1109/lpt.2009.2023234
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a-Plane Green Light-Emitting Diode Grown on r-Plane Sapphire

Abstract: Abstract-In this work, we have successfully grown a-plane green light-emitting diodes (LEDs) on r-plane sapphire and investigated the device characteristics of a-plane green LEDs. The apparent emission polarization anisotropy was observed and the polarization degree was as high as 67.4%. In addition, the electroluminescence (EL) spectra first revealed a wavelength blue-shift with increasing drive current to 20 mA, which could be attributed to the band-filling effect, and then the EL peak become constant. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…However, the device performance of these a ‐plane GaN LEDs is still poor due to the immaturity in both the growth and fabrication methods, as compared to conventional c ‐plane ones 3, 4, by which high threading dislocations, basal‐plane stacking faults and high series resistance become critical issues that need to be overcome. Nowadays, much effort has been made to solve these problems 5, 6; however, most of the reports focused on the high‐quality a ‐plane GaN growth, not much on the device and/or process optimization for current injections in this area. In fact, since the a ‐plane GaN has a different Ga‐ and N‐atom surface condition, it is of particular importance to develop a unique metal scheme suitable for such a surface condition.…”
Section: Introductionmentioning
confidence: 71%
“…However, the device performance of these a ‐plane GaN LEDs is still poor due to the immaturity in both the growth and fabrication methods, as compared to conventional c ‐plane ones 3, 4, by which high threading dislocations, basal‐plane stacking faults and high series resistance become critical issues that need to be overcome. Nowadays, much effort has been made to solve these problems 5, 6; however, most of the reports focused on the high‐quality a ‐plane GaN growth, not much on the device and/or process optimization for current injections in this area. In fact, since the a ‐plane GaN has a different Ga‐ and N‐atom surface condition, it is of particular importance to develop a unique metal scheme suitable for such a surface condition.…”
Section: Introductionmentioning
confidence: 71%
“…It was observed that the emission peak energy has a linear relationship with the current and increases with increasing current. This relationship is attributed to the electric field formed by the increased carrier concentration that decreases the impact of the quantum-confined Stark effect (QCSE) [26,34] and the energy band filling effect [35,36]. The excitons' lifetime decreased in the high-temperature range, and therefore, as the current increased the excitons could not occupy the lower energy state prior to the recombination, leading to the blue shift of the emission peak [27].…”
Section: Emission Peak Energy Vs Tjmentioning
confidence: 99%
“…Meanwhile, green light (around 510 nm) first emits from the a-plane LEDs at low current injection (0.15 mA) and then blue light emerges as the injection current is increased from 5 to 50 mA. This can be attributed primarily to the band-filling effect of the defect related stronger indium localized state 13,20 with smaller dimensions and lower density, resulting in a deeper and narrower indium localized band structure in a-plane MQWs. Figures 4(a) and 4(b) show the atomic structures of the a-plane and c-plane GaN surfaces, respectively.…”
mentioning
confidence: 99%